Influence of scars on body image consciousness with respect to gender following laparoendoscopic single-site versus conventional laparoscopic surgery. (2nd January 2017) - Yanishi, Masaaki; Kinoshita, Hidefumi; Mishima, Takao; Taniguchi, Hisanori; Yoshida, Kenji; Komai, Yoshihiro; Yasuda, Kaneki; Watanabe, Masato; Sugi, Motohiko; Matsuda, Tadashi
Abstract: Objective: The aim of this study was to evaluate and compare the cosmetic outcomes of laparoscopic single-site surgery (LESS) and conventional laparoscopy (CL) in the treatment of ureteropelvic junction obstruction (UPJO) and urachal remnant removal. LESS is thought to produce better cosmetic results than CL; however, patients' perception of their scars has not been assessed. This study compared the subjective body image and cosmesis ratings of patients who had undergone LESS or CL for UPJO and urachal remnant removal. Materials and methods: Fifty patients who underwent LESS or CL for UPJO or urachal remnant removal between June 2008 and June 2015 were included. Cosmetic outcomes were evaluated using the Body Image Questionnaire (BIQ) and Photo-Series Questionnaire (PSQ). Results: The body image and cosmetic scores were significantly higher for patients who underwent LESS than for those who underwent CL, for both pyeloplasty and urachal remnant removal ( p < .05 each). When performed for either a pyeloplasty or urachal remnant removal, significantly greater BIQ and PSQ scores were observed in females after LESS compared to CL, but not in males. Conclusion: LESS for UPJO and urachal remnant removal has better self-reported body image and cosmesis ratings than CL. This trend is particularly strong in female patients.